Pengaruh Partisipasi Penyusunan Anggaran Terhadap Kinerja Aparat Pemerintah Daerah: Desentralisasi, Gaya Kepemimpinan, Komitmen Organisasi, dan Budaya Organisasi Sebagai Variabel Moderating(Studi Empiris pada Pemerintah Daerah Kabupaten Sukoharjo) - Choiri, Anadi Miftahul (2016)
The purpose of this research is to test participation budgeting influence on the performance of the local government officials. Besides tested also decentralization role, style leadership, the organization, and culture organization as moderation on the relationship. The study sample is taken with the methods of sampling purposive namely secretary, head of division, and section head or liquid. The population of this research is in a work unit 15 ( skpd ) in government sukoharjo district. Research data used by using a questionnaire that research in send you directly to respondents. Data analyzed by the method of linear regression worship of idols The analysis data show that significantly participation budgeting variable it has some positive effects on increased performance aparan local governments. And so variable decentralization, the organization, and culture organization impact on the relationship between budgeting participation and performance regional government officials. Meanwhile, variable style leadership does not affect in moderating parisipasi budgeting influence on the performance of the local government officials.